2018
DOI: 10.3389/fninf.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Toward Rigorous Parameterization of Underconstrained Neural Network Models Through Interactive Visualization and Steering of Connectivity Generation

Abstract: Simulation models in many scientific fields can have non-unique solutions or unique solutions which can be difficult to find. Moreover, in evolving systems, unique final state solutions can be reached by multiple different trajectories. Neuroscience is no exception. Often, neural network models are subject to parameter fitting to obtain desirable output comparable to experimental data. Parameter fitting without sufficient constraints and a systematic exploration of the possible solution space can lead to concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…With the development of large-scale models such as those discussed in the previous section, the need for approaches such as computational steering in computational neuroscience is becoming apparant. Nowke et al (2018) developed a computational steering system for visualizing and steering NEST simulations. However, when running this system across a CPU-based HPC system, Nowke et al found that its scalability was dictated by the amount of data that had to be transferred across the network at each simulation timestep.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of large-scale models such as those discussed in the previous section, the need for approaches such as computational steering in computational neuroscience is becoming apparant. Nowke et al (2018) developed a computational steering system for visualizing and steering NEST simulations. However, when running this system across a CPU-based HPC system, Nowke et al found that its scalability was dictated by the amount of data that had to be transferred across the network at each simulation timestep.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we examine to what extent our main result (the sensitivity to perturbation as a unique function of the firing rate) is robust with respect to a local mechanism of firing rate homeostasis combined with a continuous weight update, as proposed by [101,102]. As described in Sec.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Their limitation lies in not being able to embody the neural simulation for instance to control a physical robot. It has also been suggested that they are less suited for evolving models (Nowke et al, 2018) because the model requires external control while evolving.…”
Section: Snn Simulatorsmentioning
confidence: 99%